Silver Nanoparticles Embedded in Natural Rubber Films: Synthesis, Characterization, and Evaluation of in Vitro Toxicity - Danna, Caroline S. [UNESP]; Cavalcante, Dalita G. S. M. [UNESP]; Gomes, Andressa S. [UNESP]; Kerche-Silva, Leandra E. [UNESP]; Yoshihara, Eidi; Osorio-Román, Igor O.; Salmazo, Leandra O.; Rodríguez-Pérez, Miguel A.; Aroca, Ricardo F.; Job, Aldo E. [UNESP] (Hindawi, 2016)
Natural rubber (NR) films can reduce silver metal ions forming embedded metal nanoparticles, a process that could be described as green synthesis. The NR films acting as a reactor generate and incorporate silver nanoparticles (AgNPs). Organic acids and amino acids play a crucial role in the formation of AgNPs. The plasmon extinction obtained in the UV-visible spectrum shows the presence of nanoparticles in the film after dipping the NR film into a solution of silver nitrate at 80°C. Electron microscopic analysis confirms the presence of AgNPs in the NR film and characterization by atomic force microscopy shows a change in the roughness of the NR film with AgNPs. In addition, our preliminary results from in vitro toxicity studies (MTT and comet assays) of the NR films and NR films with silver nanoparticles (NR/Ag) show that they are not toxic to cell lineage CHO-K1 (cells from the ovary of a Chinese hamster), an important result for potential medical applications.